Impacts of Body Shaming on the Development of Personal Values and Self- Worth Among College Students: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Body shaming has grown in popularity and is a problem that many young adults deal with on adaily basis. People fail to recognize that body shaming is a major challenge that no one istalking about and that it may have an impact on the mental health of the victim.The results showed that variables, body shame with a general weighted average of 2.94,interpreted as often; body dissatisfaction with a general weighted average of 1.6, interpretedas never; body image with a general weighted average of 1.63, interpreted as stronglydisagree, body dissatisfaction with the general weighted average of 1.6 interpreted as never,self-esteem and self-worth (positive) with the general weighted average of 1.66 interpreted asstrongly disagree, self-esteem and self-worth (negative) with the general weighted average of1.73 interpreted as strongly disagree, and personal values with the general weighted averageof 1.56 interpreted as strongly disagree. Using the T-Test Two-Sample Assuming EqualVariances was performed to calculate the impacts of body shaming on the development ofpersonal values and self-worth according to the following variables. The test findings have a P-value of 0.00872136290930584, which is less than our alpha level of significance (P< 0.05),showing that there is a significant difference resulting in rejecting the Ho.The researchers of this study have four conclusions. First, the majority of the respondents inthis study are mostly 21 years old, with a percentage of 31%. Second, respondentsencountered few challenges in terms of body dissatisfaction, while it has been seen in thefindings that most of the respondents encountered challenges in terms of body shaming.Third, it shows that body image affects the development of personal values and self-worth andthat most of the respondents show a lack of confidence and love for their bodies regardless ofwhat they wore. Lastly, the study’s overall result shows that there is a significant differencebetween the development of personal values and self-worth on body shaming when therespondents are grouped according to variables.
Keywords: Social Sciences